Práticas de gestão em redes de pequenas e médias empresas: estudo de múltiplos casos no Rio Grande do Sul - Turchetti, Marcelo (Universidade do Vale do Rio dos Sinos, 2015)
Cooperation networks of small and medium enterprises has aroused the attention of the academic world in recent decades. In order to get collective solutions these companies come together looking for results that they could not achieve alone. This research has as its theme management practices in the RS SME networks through collective action. The main objective of this work is to analyze the management practices used by top five cooperation networks classified in the ranking of GeRedes group among the networks participating in the RS government Program Cooperation Networks. The importance of the topic investigated is justified by the lack of specific studies on the management of cooperation networks. The cooperation networks are seen as a new form of organization endowed with characteristics differing networks of other forms of organization, such as, strategy, coordination, leadership, processes and interaction. A database will be used from which will be evaluated the top five networks classified in the ranking of GeRedes group. To accomplish this work, the qualitative method was used, because it is characterized as one that allows deeper understanding of the subject matter. The analysis results showed that the networks use innovative management practices to achieve their goals. It became evident that there are various types of networks, but that no network is equal to the other, even if they are based on the same concepts, using the same rules of conduct, the same coordination characteristics, the same processes and the same interaction tools.
Keywords: Redes de empresas; Redes de cooperação; Práticas de gestão; Pequenas e médias empresas; Enterprises networks; Cooperation networks; Management practices; Small and medium sized enterprises; ACCNPQ::Ciências Sociais Aplicadas::Administração